2019
DOI: 10.1177/1545968319834903
|View full text |Cite
|
Sign up to set email alerts
|

Myoelectric Computer Interface Training for Reducing Co-Activation and Enhancing Arm Movement in Chronic Stroke Survivors: A Randomized Trial

Abstract: Background. Abnormal muscle co-activation contributes to impairment after stroke. We developed a myoelectric computer interface (MyoCI) training paradigm to reduce abnormal co-activation. MyoCI provides intuitive feedback about muscle activation patterns, enabling decoupling of these muscles. Objective. To investigate tolerability and effects of MyoCI training of 3 muscle pairs on arm motor recovery after stroke, including effects of training dose and isometric versus movement-based training. Methods. We rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 43 publications
9
52
0
Order By: Relevance
“…al. found that six sessions of EMG-based training to reduce co-contraction was able to improve FMA-UE scores of 32 moderate-to-severe stroke survivors by an average of about 3 points [24]. This is the closest in design to the current study and confirms that this type of training can be of benefit in a larger population.…”
Section: Clinical Assessmentssupporting
confidence: 78%
See 3 more Smart Citations
“…al. found that six sessions of EMG-based training to reduce co-contraction was able to improve FMA-UE scores of 32 moderate-to-severe stroke survivors by an average of about 3 points [24]. This is the closest in design to the current study and confirms that this type of training can be of benefit in a larger population.…”
Section: Clinical Assessmentssupporting
confidence: 78%
“…We hypothesized that that (1) reinforcement of EMG activity in participants with severe movement deficits would be feasible, safe, and provide a positive user experience for participants; (2) training would produce modest improvements in clinical assessments comparable to what we have previously observed for EEG-based neurofeedback (i.e., variable improvement across individuals, but with some participants showing clinically meaningful effects); and (3) that we would observe evidence of improved neuromuscular control as indexed by task performance and by enhanced beta band (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) Hz) corticomuscular coherence. Finally, we expected that participants who showed strong post-training changes in clinical assessments and neuromuscular control would also show large improvements in task performance during training, assuming that within-task performance is sensitive to training-induced neural plasticity.…”
Section: Introductionsupporting
confidence: 65%
See 2 more Smart Citations
“…Almost four decades later the authors reported on similar ndings in persons with chronic stroke. The participants reduced the co-activation of arm muscles in isometric conditions using EMG biofeedback with 3 pairs of muscles in combination with computer games [13]. 32 moderately or severely impaired participants showed signi cant improvement of range of motion, muscle co-activation and a potential for reducing spasticity.…”
Section: Introductionmentioning
confidence: 99%